2020
DOI: 10.1007/s00381-020-04705-4
|View full text |Cite
|
Sign up to set email alerts
|

Neuroimaging in tuberous sclerosis complex

Abstract: Introduction Tuberous sclerosis complex (TSC) is a rare autosomal dominant disorder affecting multiple systems, due to inactivating mutations of TSC1 or TSC2 mTOR pathway genes. Neurological manifestations are observed in about 95% cases, representing the most frequent cause of morbidity and one of the most common causes of mortality. Background Neuroimaging is crucial for early diagnosis, monitoring, and management of these patients. While computed tomography is generally used as first-line investigation at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 65 publications
0
15
0
7
Order By: Relevance
“…Crucially, one such study 7 has suggested a link between postmortem dendritic synaptic surplus in ASD and hyperactivity of the mammalian target of rapamycin (mTOR) pathway 5 . mTOR is a key regulator of synaptic protein synthesis 9 , and aberrations in mTOR signaling have been linked to synaptic and neuroanatomical abnormalities 10,11 that are associated with both syndromic (e.g., tuberous sclerosis 12,13 ) and idiopathic ASD [14][15][16] . Further mechanistic investigations by Tang et al 7 , suggest that the observed excitatory spine surplus could be the result of mTOR-driven impaired macro-autophagy and deficient spine pruning, thus establishing a mechanistic link between a prominent signaling abnormality in ASD 12,16 and prevalent postmortem correlate of synaptic pathology in these disorders.…”
mentioning
confidence: 99%
“…Crucially, one such study 7 has suggested a link between postmortem dendritic synaptic surplus in ASD and hyperactivity of the mammalian target of rapamycin (mTOR) pathway 5 . mTOR is a key regulator of synaptic protein synthesis 9 , and aberrations in mTOR signaling have been linked to synaptic and neuroanatomical abnormalities 10,11 that are associated with both syndromic (e.g., tuberous sclerosis 12,13 ) and idiopathic ASD [14][15][16] . Further mechanistic investigations by Tang et al 7 , suggest that the observed excitatory spine surplus could be the result of mTOR-driven impaired macro-autophagy and deficient spine pruning, thus establishing a mechanistic link between a prominent signaling abnormality in ASD 12,16 and prevalent postmortem correlate of synaptic pathology in these disorders.…”
mentioning
confidence: 99%
“…Though Crino et al recommend annual MRI of the brain until patients are at least 21 years of age and then every 2–3 years [ 16 ], many studies recommended it once every 1–3 years until the age of 25, as new subependymal giant cell astrocytomas rarely develop after the age of 25 years [ 14 , 17 ]. These were incompatible with our case.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence indicates that the neurobiological basis of both ASD and TSC-related neurological symptoms may be due to abnormal synaptic transmission, plasticity, and alterations in neuronal connectivity as a result of pathology within synapses [ 21 , 31 , 32 ]. On the other hand, alterations in neural network connectivity in patients with TSC may result from defects in RHOA-mediated regulation of cytoskeletal dynamics during neuronal development [ 33 ].…”
Section: Introductionmentioning
confidence: 99%